Financial Performance Of Lump Auction (Case Study Of Kud Berkat In Muaraenim Regency, South Sumatra Province) - Muhamad Mustopa Romdhon; Redy Badrudin; Ulta Marta Seli (Journal of Agri Socio Economics and Business, 2021)
This study aims to analyze financial performance of at  KUD  Berkat in 2011 to 2016  and to analyze the contribution of profit share auction business unit to total profit share KUD Berkat. The study was conducted from April to May 2017. The respondents were 15 KUD officials. The financial performance KUD Berkat was analyzed with time series datMica for the 6 last years with liquidity, solvability, activity, and profitability ratios based on Regulation of State Minister of Cooperative and Small-Micro Business Republic of Indonesia Number.06/Per/M.KUKM/V/2006. The conclusion of this research is that financial analysis based on liquidity, solvability, and profitability ratios at KUD Berkat during 6 last years in healthy condition. While the activity ratio is very unhealthy. It means the turnover of receivables into cash is slow. The contribution of Auction and marketing of lump rubber to total business profit KUD Berkat at the last six years constant..